„A bym zapomniał:) Założyłem skrzynkę...”. Uwagi o etykiecie i estetyce językowej w korespondencji studentów z nauczycielami akademickimi - Pachowicz, Małgorzata (Poznańskie Spotkania Językoznawcze, 2014)
Communication in an unequal relationship (lecturer – student) is conditioned by an official communicative situation. The interchange of information in such a communicative space (situation, place and time) requires the sender and the addressee of a message to use a definite code and to observe, among others, the rules of linguistic etiquette and verbal aesthetics. In unequal relationships, it is the lecturers who in their e-mails observe the rules of linguistic etiquette and aesthetics. Students, in turn, not always can adjust their utterances to a communicative situation and consequently their linguistic behaviours are considered as unsuitable and inadequate with regard to the addressee, the situation and the act of communication. A characteristic feature of students’ letters is the use of linguistic strategies characteristic for the spoken Polish (language) in unofficial situations, and also combining the norms of linguistic polite behaviours typical for an unequal relationship as well as equal relationship.